2019
DOI: 10.1186/s40170-019-0198-7
|View full text |Cite
|
Sign up to set email alerts
|

Isocitrate dehydrogenase 1-mutated cancers are sensitive to the green tea polyphenol epigallocatechin-3-gallate

Abstract: Background Mutations in isocitrate dehydrogenase 1 ( IDH1 ) occur in various types of cancer and induce metabolic alterations resulting from the neomorphic activity that causes production of D -2-hydroxyglutarate ( D- 2-HG) at the expense of α-ketoglutarate (α-KG) and NADPH. To overcome metabolic stress induced by these alterations, IDH -mutated ( IDH mut … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…As explained above, metformin and phenformin inhibit complex I of the electron transport chain of OXPHOS and glutamate dehydrogenase, whereas chloroquine inhibits glutamate dehydrogenase ( Figure 5 ) [ 10 , 61 ]. EGCG, a major polyphenol flavonoid in green tea [ 78 ], reduces D-2-HG production and the proliferation of IDH1 mt glioblastoma cells [ 79 ]. In glioblastoma patients, EGCG seems effective only when used in large quantities as an adjuvant during radiotherapy and temozolomide chemotherapy [ 78 ].…”
Section: Energy Metabolism In Idh1 Mt Gscsmentioning
confidence: 99%
“…As explained above, metformin and phenformin inhibit complex I of the electron transport chain of OXPHOS and glutamate dehydrogenase, whereas chloroquine inhibits glutamate dehydrogenase ( Figure 5 ) [ 10 , 61 ]. EGCG, a major polyphenol flavonoid in green tea [ 78 ], reduces D-2-HG production and the proliferation of IDH1 mt glioblastoma cells [ 79 ]. In glioblastoma patients, EGCG seems effective only when used in large quantities as an adjuvant during radiotherapy and temozolomide chemotherapy [ 78 ].…”
Section: Energy Metabolism In Idh1 Mt Gscsmentioning
confidence: 99%
“…As shown in Fig. 5i, the D-2-HG biosensor B D2HG -1 could detect the increase in the levels of D-2-HG in the cell culture medium during the growth of HEK293FT cells transfected with IDH1/R132H and of HT1080 cells, a fibrosarcoma cell line carrying an IDH1/R132C mutation 30 . No D-2-HG was detected in the cell culture medium of HEK293FT cells.…”
Section: Resultsmentioning
confidence: 98%
“…Metabolomic studies of IDH1 mutant cells have revealed alterations in Gln, fatty acid, and citrate synthesis pathways [ 59 , 60 ]. IDH1 mutation was shown to convert α–KG to D–2–hydroxyglutarate, which due to its structural similarities acts as a competitive inhibitor reducing the activity of α–KG–processing enzymes [ 61 ]. As feedback, α–KG is replenished by glutaminolysis and TCA cycle, which leads to a decrease in Gln and Glu levels [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The downregulated expression is represented by blue thermometers, upregulated by red thermometers, and the non-significant differential expression in gray. Red arrows represent the activation of the pathway and blue arrows represent the inactivation of the pathway shown to convert α-KG to D-2-hydroxyglutarate, which due to its structural similarities acts as a competitive inhibitor reducing the activity of α-KG-processing enzymes [61]. As feedback, α-KG is replenished by glutaminolysis and TCA cycle, which leads to a decrease in Gln and Glu levels [62].…”
Section: Discussionmentioning
confidence: 99%